Reproductive Performance of Rex and Rex-Satin Cross (Reza) Does and Their Bunny Growth in Tebonan Village, Hargobinangun, Pakem, Sleman - Dewi Pranatasari; Ismaya -; Panjono - (Universitas Tidar, 2021)
This study aimed to observe Rex and Rex-Satin cross (Reza) does and their bunny ‘growth rate in Tebonan village, Hargobinangun, Pakem, Sleman. Two groups contain five of five- to eight-month-old Rex and Reza, respectively, were used in this study. Rabbits were reared in an individual wire hutch and fed with commercial feed and pasture i.e. groundnut straw or corn fodder. They were mated with the buck from the same breeds for each group. Data were analyzed using statistical analysis of independent sample T-test. Service per conception, gestation length, litter size, birth weight, litter weight, and mortality rate in Rex and Reza were 1.00±0.00 and 1.20±0.45 times, 32.20±1.48 and 32.20±1.30 days, 5.20±1.79 and 4.60±2.19 tails, 86.85±27.39 and 71.17±25.45 g, 412.80±137.78 and 336.68±168.40 g, and 10.00±14.91 and 30.00±27.39 % respectively. The bodyweight of bunny of Rex and Reza at one to four weeks of age were 170.83±69.96 and 148.09±47.24 g, 227.10±98.36 and 196.83±32.73 g, 286.60±135.76 and 233.30±29.01 g, and 341.13±158.19 and 304.70±49.44 g, respectively. It was concluded that the gestation length, litter size, birth weight, and litter weight of Rex and Reza were similar. Service per conception and bunny’s mortality rate of Rex does were higher than those of Reza does. Bunny’s growth rate of both breeds was similar.